Utilization of air-plasma treated waste polyethylene terephthalate particles as a raw material for particleboard production. (1st April 2016) - Klímek, Petr; Morávek, Tomáš; Ráhel, Jozef; Stupavská, Monika; Děcký, David; Král, Pavel; Kúdela, Jozef; Wimmer, Rupert
Abstract: Wood-plastic composite boards involving up to 30 wt. % of polyethylene terephthalate (PET) flakes were evaluated for its physical and mechanical properties – internal bonding strength, modulus of rupture and thickness swelling. It was found that the problem of the decline of mechanical properties can be successfully mitigated by air plasma pretreatment of PET flakes. The samples with 30 wt. % of plasma treated PET exhibited the same internal bonding strength as the control pure wood sample; samples with 15 wt. % of plasma treated PET exhibited the same modulus of rupture. The role of plasma treatment is to generate chemically active functional groups to PET flakes surface. This was verified by measuring the thermal chemiluminescence of plasma treated flakes.